Effect of pH and calcium chloride on the thermal inactivation kinetics and stability of chlorophyllase in mulberry leaves - Yali Zhao; Xunwen Liu; Shenye Qian; Jinwen Lu; Xintong Liu; Chunfang Cai; Xiamin Cao (Applied Food Research)
This study assessed the effect of pH (5.7, 6.8, and 8.0, adjusted using phosphate buffer) and calcium chloride (0.2 g kg-1, 0.6 g kg-1, and 1.0 g kg-1) on the chlorophyllase (Chlase) activity and thermal inactivation in mulberry leaves at temperatures ranging from 75 ℃ to 100 ℃. The overall lethality was calculated, and the subsequent data were described using a two-fraction kinetics model. The results showed that the Chlase activity displayed an initial increase at a higher pH level and calcium chloride concentration, followed by a decline. Furthermore, the pH and calcium chloride also affected the Chlase inactivation kinetics. Weak acidity (pH 5.7) distinctly promoted Chlase inactivation during thermal treatment, while weakly alkaline conditions (pH 8.0) enhanced heat stability. The presence of calcium chloride increased the Chlase thermal stability, while the response to thermal processing (TP) varied depending on the calcium chloride concentration.